Development of Single-Board Computer Based Web Server for Physics Related Instrumentation and Its More General Usage - Endarko Endarko; Zaki Su’ud (Indonesian Journal of Physics, 2003)
The web server single-board provides web access to some digital I/O and serial I/O signals without the need for assistance from external PCs or UNIX computers. It’s stand-alone device with real-time networking kernel, a TCP/IP stack, and HTTP web server. This project started partly as an excuse to use a new microprocessor and partly to settle a long-standing argument about the possibility of delivering web pages with a commercial microcontroller. The Atmel AT90S8515 microprocessor looked exciting with it’s low power RISC processor, 8 KB flash program memory, 512 bytes of EEPROM, 512 bytes of RAM, 32 I/O lines, and a built-in UART. The proposed device is designed application for physics related instrumentation and its more general usage.